β-hydroxybutyrate Alleviates Learning and Memory Impairment Through the SIRT1 Pathway in D-Galactose-Injured Mice - Yang, Xiaojing; Wang, Ruonan; Zhou, Hailun; Wang, Li; Wang, Rui; Li, Haomin; Tan, Baodong; Wu, Qiong; Xu, Xin; Cui, Lianxu; Li, Zaiyu; Li, Hua (Frontiers in Pharmacology, 2021)
Learning and memory impairment is a common clinical symptom of aging and the nervous system injuries and seriously affects the quality of life. Memory impairment is associated with increased oxidative stress(OS) and inflammatory response. β-hydroxybutyrate (BHBA) is a water-soluble endogenous small molecule ketone body that easily crosses the blood-brain barrier and has shown neuro-protection activities. In this study, we investigated the effects and mechanisms of BHBA on D-galactose (D-gal)-induced memory impairment in mice by in vitro and in vivo experiments. BHBA was administered intragastrically to D-gal injured C57BL/6 mice for 42 days. Water maze performance, morphology of hippocampus with Nissl staining, ACh content, OS and inflammation status were examined. To further investigate the mechanism, hippocampal neuronal cells (HT22) were treated with BHBA with or without SIRT1 inhibitor or small interfering RNAs against sirt1 (si-SIRT1) before incubation with D-gal. BHBA improved significantly water maze performance, increased ACh content, SOD activity and SIRT1 expression, and decreased AChE and LDH activity, ROS, MDA, IL-1β, TNF-α contents and NLRP3 expression. Further studies with SIRT inhibitor or siRNAs against sirt1 reversed the above effects by BHBA. Collectively BHBA inhibited hippocampal OS and inflammation process to alleviate learning and memory impairment through activating SIRT1 pathway in D-gal-injured mice, suggesting BHBA be a potential option for drug development of learning and memory impairment induced by nervous system injuries.